A Case of Thyroidal Coccidioidal Infection - Nadia Raza MD; Arash Heidari MD (SAGE Publishing, 2022)
Infection of the thyroid gland with Coccidioides immitis is rare. We report a case with disseminated coccidiomycosis involving thyroid gland as a thyroid nodule. Although historical autopsy studies have indicated that coccidioidal involvement of the thyroid gland can infrequently occur as part of disseminated infection, to our knowledge, only less than 10 other cases have been reported. Optimal treatment duration and dosage of medication are uncertain in literature of this rare involvement of thyroid gland with coccidioidomycosis.